PENGARUH PENDAPATAN KELAPA SAWIT TERHADAP PDRB KABUPATEN BUNGO - Asminar Asminar (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
Palm oil is the prime commodity in Indonesia so that it can absorb a lot of energy and increase community income. The purpose of this study is. The purpose of this study was to determine the development of land area and oil palm production in Bungo District and determine the effect of oil palm income on oil palm GRDP in Bungo.The type of data used in this study is secondary data, namely time series data in the span of years 2007 to 2016. Secondary data in this study are the area of oil palm, oil palm production, agricultural GRDP and PDRB Bungo District. The method used to determine the development of land area and oil palm production in Bungo District with descriptive analysis and simple linear regression. The results showed that the development of the area of oil palm in Bungo district always increased from year to year and oil palm production in Bungo Regency always fluctuated. The year 1999 experienced a decline in 2001 began to increase slowly and in 2013 experienced a very significant increase of 559,666,000 kg and the effect of oil palm income on oil palm GRDP in Bungo District had an effect with an Adjusted R Square value of 0.800. This showed that palm oil income affected Bungo Regency's GRDP is 80%, the remaining 20% is caused by other influences